2011
DOI: 10.1021/ja205716t
|View full text |Cite
|
Sign up to set email alerts
|

Facile Charge-Displacement at Silicon Gives Spaced-out Reaction

Abstract: Adsorbates on metals, but not previously on semiconductors, have been observed to display long-range repulsive interactions. On metals, due to efficient dissipation, the repulsions are weak, typically on the order of 5 meV at 10 Å. On the 7×7 reconstruction of the Si(111) surface, charge transport through the surface has been demonstrated by others using charge injection by STM tips. Here we show that for both physisorbed brominated molecules, and for chemisorbed Br-atoms, induced charge-transfer in the Si(111… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Charge-transfer through the surface has been studied extensively for various reactions on metal and on semiconductor surfaces. ,,, For single H-atoms at Si(100), Radny et al found, as here, that the charge in the adjacent dangling bond was transferred along the dimer row rather than across . Charge flow along dimer-rows has also previously been noted in theoretical studies of adsorption of O- and N-containing molecules on the surface studied here; Si(100). …”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Charge-transfer through the surface has been studied extensively for various reactions on metal and on semiconductor surfaces. ,,, For single H-atoms at Si(100), Radny et al found, as here, that the charge in the adjacent dangling bond was transferred along the dimer row rather than across . Charge flow along dimer-rows has also previously been noted in theoretical studies of adsorption of O- and N-containing molecules on the surface studied here; Si(100). …”
Section: Introductionsupporting
confidence: 65%
“…We calculated the substantial difference of 0.5 electrons between the OD site and the ID site. Since Br radicals are known to prefer an electron-rich environment, ,, the increased charge adjacent to a reacted H favored ID reaction by the Br-atom.…”
Section: Theoretical Resultsmentioning
confidence: 99%
“…The 70 meV difference in E a corresponds to a fifteen-fold difference in reactivity at room temperature. The structures shown here were calculated at a lower level of theory (see ESIz), known from other work, 12 to give good physisorption geometries and energetics for halogenated alkanes on silicon surfaces, but which does not recover the surface buckling at dimers adjacent to the adsorbates.…”
Section: Communicationmentioning
confidence: 99%
“…The products of thermal reaction are chemisorbed bromine atoms, identified by the characteristic lighting‐up at a sample bias between +1.0 V and +2.5 V,5a and confirmed by the thermal stability of the features for days at 300 K, in contrast to the spontaneous dissociation6b of physisorbed PeBr at the same temperature. Product bromine atoms exclusively chemisorbed at the prior physisorption sites, as shown in Figure 2 a–d.…”
Section: Comparison Of Measured Activation Energies For V and H Statementioning
confidence: 88%
“…Studies in this laboratory of the adsorption and reaction of haloaromatics5 and haloalkanes6 at silicon surfaces, using scanning tunneling microscopy (STM), provided evidence of vertical, v , and horizontal, h , states of single adsorbates at Si(111)‐7×7; examples being 1‐bromopropane,6a,b 1‐bromopentane,6c 1‐chlorododecane,6df and 1‐bromododecane 6e,f. Experimentally, the assignment of adsorbate alignment ( v vs h ) is based on contrasting surface mobilities6af ( v more mobile than h ) and sometimes differing STM imaging6ac ( v higher than h ).…”
Section: Comparison Of Measured Activation Energies For V and H Statementioning
confidence: 99%